The Relationship Between the Application of the Team's Professional Nursing Care Method (MAKP) with Nurse Performance in the Internal Inpatient Room of Dr. M.M Dunda Limboto Hospital, Gorontalo Regency - Firmawati Firmawati; Euis Herawati Hidayat; Azzahra Imansari Mahmud (Universitas Ibn Khaldun Bogor, 2023)
Performance is an action taken by a nurse in an organization by their respective authorities and responsibilities. Improve performance and improve nurse performance, one of them is by applying the Professional Nursing Care Method (MAKP) team to improve the quality of nurse performance. The purpose of the study was to analyze the application of the Nursing Care Method (MAKP) Team with nurse performance. Quantitative research design with cross-sectional approach. The population is 52 people with total sampling techniques so the number of samples is 52 people. The results showed that most TIM nursing care methods were optimal for as many as 35 people with good performance in as many as 36 people, pValue value = 0.000<0.05. Conclusion There is a relationship between the Application of the Nursing Care Method (MAKP) Team with the Performance of Nurses at RSUD dr. M.M. Dunda Limboto, Gorontalo Regency. Suggestions are expected to be input for RSUD dr. M.M. Dunda Limboto in improving service and satisfaction to patients and also for the welfare of nurses who work.